(untitled) (Revista de Ciências Agroveterinárias, 2011)
White mold caused by Sclerotinia sclerotiorum is one of the most destructive diseases of soybean crop in Southern Brazil. The pathogen can survive in the soil through its resting structures, the sclerotia. This work aimed to identify substrates for induction of carpogenic germination of sclerotia and their viability. Sclerotia used throughout this work were naturally produced in infected soybean plants on a commercial farm in Coxilha county, RS. Sclerotia were separated manually and then those with five to seven mm of length and approximately three millimeters of diameter were selected. The carpogenic germination was determined in the laboratory by growing the sclerotia on five substrates: sterilized coarse sand, vermiculite, water - agar 1%, water - agar 1% + streptomycin sulphate and sterile water. The evaluation of the esclerotia viability was performed at 10 day intervals, counting those with formed apothecia up to 120 days. Water-agar, coarse sand and vermiculite promoted higher speed and fi nal percentage of carpogenic germination of esclerotia, resulting in 50% of germination in 40 days. Lower speed and slower germination occurred with sterile water and water + streptomycin-sulphate.